2009
DOI: 10.2343/geochemj.1.0037
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of non-radiogenic tungsten isotopic anomalies in the Allende CV3 chondrite

Abstract: We have measured high-precision W isotope ratios for series of carbonaceous and ordinary chondrites. could not be attributed to the incomplete digestion of acid-resistive presolar components such as SiC grains with abundant s-process nuclides, because the SiC contents in the Allende was significantly lower than those for other carbonaceous chondrites. Several possible explanations for the deficiency in the 184 W found in the Allende CV3 were explored. We conclude the results could be best explained by the isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The variability in isotopic ratios of non-radiogenic isotopes now extends to approximately 25% for oxygen (Clayton et al 1973;Kobayashi et al 2003;Sakamoto et al 2007) and typically much less than 0.01% for most other elements Dauphas et al 2002Dauphas et al , 2008Yin et al 2002a;Andreasen and Sharma 2006;Ranen and Jacobsen 2006;Carlson et al 2007;Quitte´et al 2007Quitte´et al , 2010Trinquier et al 2007Trinquier et al , 2009Yokoyama et al 2007;Chen et al 2009Chen et al , 2010Irisawa et al 2009;Reisberg et al 2009;Moynier et al 2010;Burkhardt et al 2011;Qin et al 2011;Huang et al 2012). Thus, reasonably good (but not perfect) mixing of the isotopes appears to be dominant in bulk meteorite samples and in most macroscopic inclusions (e.g., see fig.…”
Section: Heterogeneity Of 26 Al ⁄ 27 Al In the Solar Systemmentioning
confidence: 99%
“…The variability in isotopic ratios of non-radiogenic isotopes now extends to approximately 25% for oxygen (Clayton et al 1973;Kobayashi et al 2003;Sakamoto et al 2007) and typically much less than 0.01% for most other elements Dauphas et al 2002Dauphas et al , 2008Yin et al 2002a;Andreasen and Sharma 2006;Ranen and Jacobsen 2006;Carlson et al 2007;Quitte´et al 2007Quitte´et al , 2010Trinquier et al 2007Trinquier et al , 2009Yokoyama et al 2007;Chen et al 2009Chen et al , 2010Irisawa et al 2009;Reisberg et al 2009;Moynier et al 2010;Burkhardt et al 2011;Qin et al 2011;Huang et al 2012). Thus, reasonably good (but not perfect) mixing of the isotopes appears to be dominant in bulk meteorite samples and in most macroscopic inclusions (e.g., see fig.…”
Section: Heterogeneity Of 26 Al ⁄ 27 Al In the Solar Systemmentioning
confidence: 99%
“…The study of mass independent fractionation of W isotopes is of great interest for chronological purposes [1][2][3][4][5][6][7][8][9] and for understanding nucleosynthetic processes and subsequent dynamical processes in the solar nebula. [10][11][12] The 182 Hf-182 W chronometer is well-suited to date, for instance, the formation of iron meteorites, 2,6,[13][14][15] the metamorphism of H-chondrites, 16 or the metal-silicate segregation in achondrites, 5,7,8,[17][18][19] thus proving to be useful in understanding the rst stages of solar system history and planetary formation. Tungsten isotope measurements are usually performed aer separation of W from the matrix elements using an anion-exchange resin, and involve mass spectrometry techniques, be it multi-collector inductivelycoupled plasma mass spectrometry 1,6,13,15,16 (MC-ICMPS) or negative ion thermal ionization mass spectrometry 20,21 (N-TIMS).…”
Section: Introductionmentioning
confidence: 99%
“…Kleine et al (2004) measured the 183 W/ 184 W ratios in a variety of chondrites as well as eucrites and Martian meteorites, and found no detectable isotope anomalies. Irisawa et al (2009) measured W isotope ratios for a suite of carbonaceous and ordinary chondrites and found a small deficit in 184 W/ 183 W at a level of ~0.4ε for the Allende meteorite (CV3), but not for the other chondrites. These authors argued that the observed anomalies could not be due to the incomplete digestion of presolar SiC grains because the amount of surviving presolar SiC in Allende is significantly lower than for most other carbonaceous chondrites.…”
Section: Yokoyama and Walkermentioning
confidence: 99%